2009
DOI: 10.1542/peds.2008-2198
|View full text |Cite
|
Sign up to set email alerts
|

Acute Heart Failure Syndromes in the Pediatric Emergency Department

Abstract: These data yield important insight into the clinical features and initial treatment of children who present with AHFS in the ED and may allow for improved recognition and treatment of this clinical syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 18 publications
0
36
0
3
Order By: Relevance
“…These infants also had longer LOS and more PICU admissions [5]. The diagnosis of HF in these patients may be of help in the early assessment and management in the ED [3]. In our study, all patients recovered; however, the cohort who had HF had a significantly longer LOS, and 3 (43%) of 7 patients were admitted to the PICU.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These infants also had longer LOS and more PICU admissions [5]. The diagnosis of HF in these patients may be of help in the early assessment and management in the ED [3]. In our study, all patients recovered; however, the cohort who had HF had a significantly longer LOS, and 3 (43%) of 7 patients were admitted to the PICU.…”
Section: Discussionmentioning
confidence: 53%
“…In recent years, following studies in adults, BNP has been extensively studied in pediatrics for the early diagnosis of cardiac disease as well as assessment of heart failure (HF) in a multitude of clinical situations [1,2]. The diagnosis of pediatric HF in the emergency department (ED) is challenging due to nonspecific symptoms and signs [3]. A previous pediatric study compared noncardiac patients who presented with respiratory symptoms with cardiac patients who presented with HF and reported that the BNP can be a useful test to differentiate between the 2 groups [4].…”
Section: Introductionmentioning
confidence: 99%
“…Because of faster ventricular rates and their inability to verbalize their symptoms, infants usually show typical heart failure symptoms (respiratory distress, diaphoresis, and poor feeding) earlier. On the other hand, older children may present with palpitation, exercise intolerance, chest pain or syncope (15). As the underlying tachyarrhythmia may not be apparent, a high index of suspicion is the most important step for diagnosis of TIC.…”
Section: Discussionmentioning
confidence: 99%
“…Infants are recognized on the basis of respiratory distress, diaphoresis, and poor feeding, while older children may present with exercise intolerance, dyspnea on exertion, chest pain, or syncope [3, 4]. Older children may describe palpitations though this is not always reliable.…”
Section: Discussionmentioning
confidence: 99%